Simple technique for fabrication of shielding blocks for total body irradiation at extended treatment distances - Ravichandran, R. (Medknow Publications, 2009)
Techniques are being standardized in our department for total body irradiation (TBI) with six MV photons in linear accelerator for preconditioning to bone marrow transplantation (BMT). Individualized shields with low melting point alloy are to be fabricated for shielding critical organs such as lungs, kidneys etc. A method to mount diminished dimension of shields in a tray at 3.75m is designed in the department for a teletreatment distance of four meters with magna field with A simulator image taken with the patient's midplane (MP) at one meter distance is used to mark the dimensions of lung, scaled down by a factor of 3.75/4.0. These lung dimensions are reprinted from the digital simulator image for making the shield. The methodology of the technique using digitized minification in radiography is the first of its kind to be used for shield cutting in magna field radiotherapy.